THE LEADERSHIP OF INTEGRATED TOURISM AND DEVELOPMENT STRATEGY MERGING BETWEEN CONSERVATIVE AND MODERN TOWARDS THE WORLD CLASS RANKING STATUS: A CASE STUDY OF THE COASTAL CITIES IN THE UPPER SOUTHERN REGION OF THAILAND - พันธุ์เอี่ยม กาญจนา (RMUTT Global Business and Economics Review, 2015)
The main object in this dissertation is to study and analyze ideas and attitude of leaders and leadership about the integrated Tourism and strategic development mixing with conservatives and modern style presentation the pattern of world level status the future: A Case Study of The coastal Cities in The Upper Southern Region of Thailand The methodology used both in qualitative and quantitative research collected by in-depth interviews the key Informants group and 50 expert’s who had been directly affected from leader group, executives, political representative both the national and local level, government and private sector, academic sector both in strategic leadership and tourism and mass communication both in religion and community leader. Then the data from a qualitative study has been taken to study the quantitative research methods by using questionnaires that were created to poll the members of 286 Local Administrative Leadership as models. The research result, it shows the overview as “The Leadership of Integrated Tourism and Development Strategy merging between Conservative and Modern Towards The World Class Ranking Status : A Case Study of The coastal Cities in The Upper Southern Region of Thailand” in the past, present and also future which it can describe the analysis of data in both qualitative and quantitative forms from “ The Classic Vintage Destination” To “The NeoRenaissance Rendezvous” The study suggested that, the Integrated Tourism Leaderships must be modified from the role “ The Classic Vintage Destination” To “The Neo-Renaissance Rendezvous” make it beneficial for Mixed Conservative – Modern Development Strategy Towards The World Class Ranking Status of the Upper Southern Region of Thailand in the Future.